Rethinking Britain : policy ideas for the many - Konzelmann, Suzanne J.; Himmelweit, Susan; Smith, Jeremy; Weeks, John, 1941- (Bristol, UK ; Chicago, IL, USA : Policy Press, 2019)
What if we had a government prepared to implement the policies that could radically change 21st-century Britain and improve people's lives? Social and economic policies are rarely communicated clearly to the public, but it's never been more important for citizens to understand and contribute to the debate around the country's future. In everyday language, Rethinking Britain presents a range of ideas from some of the country's most influential thinkers such as Kate Pickett and Ha-Joon Chang. From inflation to tax, and health to education, each contribution offers solutions which, if implemented, would lead to a fairer society. Curated by leading economists from the Progressive Economics Group and accompanied by a 'jargon buster', this book is an essential aid for citizens who are interested in critiquing inequalities while looking to build a better future.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: Social justice -- Great Britain; Great Britain -- Social conditions -- 21st century; Great Britain -- Politics and government -- 2007-